Experimental Results for the Multipath Performance of Galileo Signals Transmitted by GIOVE-A Satellite. (29th April 2008) - Simsky, Andrew; Mertens, David; Sleewaegen, Jean-Marie; Hollreiser, Martin; Crisci, Massimo
Abstract : Analysis of GIOVE-A signals is an important part of the in-orbit validation phase of the Galileo program. GIOVE-A transmits the ranging signals using all the code modulations currently foreseen for the future Galileo and provides a foretaste of their performance in real-life applications. Due to the use of advanced code modulations, the ranging signals of Galileo provide significant improvement of the multipath performance as compared to current GPS. In this paper, we summarize the results of about 1.5 years of observations using the data from four antenna sites. The analysis of the elevation dependence of averaged multipath errors and the multipath time series for static data indicate significant suppression of long-range multipath by the best Galileo codes. The E5AltBOC signal is confirmed to be a multipath suppression champion for all the data sets. According to the results of the observations, the Galileo signals can be classified into 3 groups: high-performance (E5AltBOC, L1A, E6A), medium-performance (E6BC, E5a, E5b) and an L1BC signal, which has the lowest performance among Galileo signals, but is still better than GPS-CA. The car tests have demonstrated that for kinematic multipath the intersignal differences are a lot less pronounced. The phase multipath performance is also discussed.